2019
DOI: 10.1111/luts.12272
|View full text |Cite
|
Sign up to set email alerts
|

Tadalafil, a phosphodiesterase type 5 inhibitor, restores urethra and detrusor function in the initial phase of diabetes in rats

Abstract: Objective This study investigated the effects of tadalafil on the urethra and detrusor in the initial phase of diabetes in rats. Methods Thirty‐six female Sprague‐Dawley rats were assigned to a non‐diabetes (ND), diabetes (D), or tadalafil‐treated diabetes (DT) group (n = 12 per group), with the DT group receiving oral tadalafil (2 mg/kg/d) for 7 days before the experiments. Seven weeks after diabetes induction (by a single intraperitoneal injection of streptozotocin), urethral and intravesical pressure were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, it was in fact opposite. We presumed that the higher maximal voiding pressure and opening pressure demonstrated in the DM rats may be due to urethral relaxant dysfunction during voiding, as this type of urethral dysfunction was reported at an early phase (5-7 weeks) of STZ-induced DM rats 7,8 . To determine whether urethral relaxant dysfunction occurs also in the present (16 weeks STZ-induced) DM rats, we performed simultaneous recordings of bladder pressure under isovolumetric conditions and UPP.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, it was in fact opposite. We presumed that the higher maximal voiding pressure and opening pressure demonstrated in the DM rats may be due to urethral relaxant dysfunction during voiding, as this type of urethral dysfunction was reported at an early phase (5-7 weeks) of STZ-induced DM rats 7,8 . To determine whether urethral relaxant dysfunction occurs also in the present (16 weeks STZ-induced) DM rats, we performed simultaneous recordings of bladder pressure under isovolumetric conditions and UPP.…”
Section: Discussionmentioning
confidence: 97%
“…Torimoto et al reported that diabetic urethral dysfunction associated with NO deficiency occurred at an early phase (at 5 weeks) 7 . Gotoh et al reported that tadalafil restored bladder blood flow and lower urinary tract function, including urethral function, at an early phase of DM (at 7 weeks) 8,17 . Our results suggest that long-term diabetes caused NO/cGMP deficiency, resulting in urethral relaxant dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, tadalafil might intensify the action of NO and relieve urethral resistance regardless of the presence or absence of BOO. In fact, tadalafil has been reported to restore urethral relaxation function in the initial phase of a diabetes‐induced DU rat model 23 . It was considered that the difference in these actions between the two drugs might influence the difference in the improvement of voiding functions, such as Qmax.…”
Section: Discussionmentioning
confidence: 99%
“…Seven weeks after STZ injection in rats, a 7-day treatment with tadalafil restored prolonged inter-contraction intervals and diminished bladder blood flow to values comparable to those in control animals (Gotoh et al 2018 ). In a follow-up study, tadalafil restored urethral relaxation and detrusor contraction (Gotoh et al 2019 ). Restoration of detrusor function by tadalafil in UAB observed at late time points after administration of STZ was also reported by others (Masuda et al 2020 ).…”
Section: Effects Of Established Medications On Lutd In Diabetesmentioning
confidence: 99%